الإسلاموفوبيا الشبكية: المنشورات الفلسطينية؛ نموذجا. - بليل, عبد الكريم (جامعة الوادي - University of Eloued, 2022)
لظاهرة الإسلاموفوبيا أبعاد تاريخية وانفعالات دينية وسياسية قديمة. نمت مع تطورات صراع أوروبا ضد التوسع الإسلامي. فاستوطنت في أدب المستشرقين، ثم تسللت إلى الأدباء والفلاسفة وغيرهم، ليكتسي الفكر الغربي في الإعلام الكلاسيكي بها، نحو تكريس صورة نمطية سوداوية ظلامية. أصبحت أكثر قتامة؛ مع استراتيجية أمريكا لمكافحة الإرهاب، وتضخمت في عالم الويب. ورغم تحديد الأخلاقيات الرقمية لمكافحة العنف الإلكتروني والمنشورات التحريضية، ضمن المبادئ العامة لمجتمع المعلومات. إلا أن قضايا الأمن السيبراني الشبكي المتتالية؛ كشفت عن ازدواجية في تطبيق المعايير الأخلاقية الرقمية. فهي مطبقة بصرامة على أطراف وقضايا معينة، بينما تفقد مصداقيتها وتتلاشى مع أطراف وقضايا أخرى. هل فرضت منصات التواصل الاجتماعي قواعد رقمية غير عادلة على الرواية الفلسطينية؟ نهدف في هذا البحث إلى كشف تقنيات الذكاء الاصطناعي في تغذية الإسلاموفوبيا، ونماذج دعم التطرف ضد المسلمين وقضاياهم، وقمع رواية أي طرف مسلم يدافع عن حقه في محاربة ظلم الاحتلال وجماعاته المتطرفة في فلسطين. أهم النتائج: - فرضت منصات التواصل الاجتماعي قواعد أخلاقية رقمية غير عادلة ومتحيزة في أحكامها وتطبيقاتها. - البرمجة الخوارزمية. مسؤول عن حجب المنشورات التي تدعم الفلسطينيين. - كشفت معركة غزة عن الأخلاق الرقمية الدنيئة للمواطن الرقمي الصهيوني، حيث حوّل الضحية إلى جلاد، واختلق الأخبار. - تم إطلاع المتابعين على مدى عنصرية منصات التواصل الاجتماعي بتجاهلها للتضليل والتلفيق والتحريض على العنف الصادر من الاحتلال الصهيوني. Abstract : The phenomenon of Islamophobia has historical dimensions and ancient religious and political emotions. It grew with the developments of Europe's struggle against Islamic expansion. It settled in the literature of orientalists, and then infiltrated the writers, philosophers and others, to cover Western thought in the classical media, towards perpetuating a dark and dark stereotyped image. Became darker; With America's anti-terror strategy, the web world has swelled. which, despite defining digital ethics to combat electronic violence and inflammatory publications, within the general principles of the information society; However, the successive network cybersecurity issues; It revealed double standards in the application of digital ethical standards. It is strictly applied to certain parties and issues, while it loses its credibility and fades with other parties and issues. Have social media platforms imposed unfair digital rules on the Palestinian narrative? We aim in this research to expose artificial intelligence techniques that fuel Islamophobia, and models for supporting extremism against Muslims and their issues, and to suppress the narrative of any Muslim party defending its right to fight the oppression of the occupation and its extremist groups in Palestine. The most important results: Social media platforms have imposed unfair and biased digital ethical rules in their judgments and applications. Algorithmic programming. Responsible for blocking only publications that support the Palestinians. - The battle of Gaza revealed the despicable digital morals of the Zionist digital citizen, as he turned the victim into an executioner, and made up the news. - Followers wereinformed of the extent of the racism of social media platforms by ignoring misinformation, fabrication and incitement to violence stemming from the Zionist occupation.
مقال
Keywords: الإسلاموفوبيا الشبكية. ; الأخلاقيات الرقمية ; الذكاء الاصطناعي ; منصات التواصل الاجتماعي ; المنشورات الفلسطينية